Overview of groundwater in the Nile River Basin. - MacAlister, C.; Pavelic, Paul; Tindimugaya, C.; Ayenew, T.; Ibrahim, M. E.; Meguid, M. A. (Routledge, 2012)
Groundwater is gaining increasing recognition as a vital and essential source of safe drinking water throughout the Nile Basin, and the demands in all human-related sectors are growing. The technical and regulatory frameworks to enable sustainable allocation and use of the resource, accounting for environmental service requirements, are largely not in place. The hydrogeological systems, and the communities they support, are highly heterogeneous across the basin, ranging from shallow local aquifers (which are actively replenished by rainfall recharge, meeting village-level domestic and agricultural needs) through to deep regional systems (which contain non-replenishable reserves being exploited on a large scale). A uniform approach to management under such circumstances is inappropriate. The database and monitoring systems to support groundwater management are weak or non-existent. With few exceptions, groundwater represents an unrecognized, shared resource among the Nile countries. Most Nile countries have strategic plans to regulate and manage groundwater resources but, so far, these largely remain on paper, and have not been implemented.